OPTIMIZATION OF IMPLEMENTATION OF THE ISLAMIC SOCIAL ENTERPRISE IN MUHAMMADIYAH HIGHER EDUCATION - Junarti, Junarti; Astuti, Tri Budi; Husnayetti, Husnayetti (Ekonomi Islam, 2025)
Research Aims: This study aims to optimize the implementation of Islamic Social Enterprise (ISE) in Muhammadiyah higher education institutions by identifying challenges and opportunities. It seeks to develop a framework to enhance the role of these universities as socially responsible organizations guided by Islamic values. Design/Methodology/Approach: A qualitative approach is used, involving case studies and in-depth interviews with university leaders, social enterprise managers, faculty, and students engaged in ISE activities. Data are collected through document analysis and thematic coding to uncover key factors affecting ISE success. Research Findings: Findings show Muhammadiyah universities have initiated ISE activities but face challenges such as limited awareness, resource shortages, and weak integration of ISE principles in strategy. Successful cases highlight leadership commitment, community involvement, and clear governance as critical to improving social and financial outcomes. Theoretical Contribution/Originality: This research contributes by linking Islamic social entrepreneurship with higher education management, presenting a unique model tailored to Muhammadiyah universities. It integrates Islamic ethics and social enterprise theory, offering fresh insights into value-driven institutional practices. Practitioners/Policy Implications: The study provides practical recommendations for university leaders and policymakers, including enhanced training on Islamic entrepreneurship, stronger community partnerships, and better resource management to support sustainable ISE development. Research Limitations/Implications: Limitations include the focus on Muhammadiyah institutions, limiting wider applicability, and reliance on qualitative data, which restricts measurable impact assessment. Future studies should expand scope and use mixed methods to further validate and improve the ISE implementation model.